Improved Ca2+ release synchrony following selective modification of Itof and phase 1 repolarization in normal and failing ventricular myocytes. (November 2022) - Fowler, Ewan D.; Wang, Nan; Hezzell, Melanie J.; Chanoit, Guillaume; Hancox, Jules C.; Cannell, Mark B.
Abstract: Loss of ventricular action potential (AP) early phase 1 repolarization may contribute to the impaired Ca 2+ release and increased risk of sudden cardiac death in heart failure. Therefore, restoring AP phase 1 by augmenting the fast transient outward K + current (Itof ) might be beneficial, but direct experimental evidence to support this proposition in failing cardiomyocytes is limited. Dynamic clamp was used to selectively modulate the contribution of Itof to the AP and Ca 2+ transient in both normal (guinea pig and rabbit) and in failing rabbit cardiac myocytes. Opposing native Itof in non-failing rabbit myocytes increased Ca 2+ release heterogeneity, late Ca 2+ sparks (LCS) frequency and AP duration. (APD). In contrast, increasing Itof in failing myocytes and guinea pig myocytes (the latter normally lacking Itof ) increased Ca 2+ transient amplitude, Ca 2+ release synchrony, and shortened APD. Computer simulations also showed faster Ca 2+ transient decay (mainly due to fewer LCS), decreased inward Na + /Ca 2+ exchange current and APD. When the Itof conductance was increased to 0.2 nS/pF in failing cells (a value slightly greater than seen in typical human epicardial myocytes), Ca 2+ release synchrony improved and AP duration decreased slightly. Further increases in Itof can cause Ca 2+ release to decrease as the peak of the bell-shaped ICa -voltage relationship is passed and premature AP repolarization develops. These results suggest that there is an optimal range for Itof enhancement that may support Ca 2+ release synchrony and improve electrical stability in heart failure with the caveat that uncontrolled Itof enhancement should be avoided. Graphical abstract: Graphical abstract Unlabelled Image Highlights: Loss of fast transient outward current alters phase 1 of the cardiac AP in HF. By computing and injecting a synthetic transient outward current phase 1 was altered. Moderate increases in transient outward current improves Ca release synchrony. Reduced arrhythmogenic late Ca sparks in heart failure accompany phase 1 restoration There is a limited therapeutic window for transient outward current augmentation.